EVALUATION OF SEX-SPECIFIC DIFFERENCES OF ANTHROPOMETRIC VARIABLES THAT WERE USED AS INDICATORS OF NUTRITIONAL STATUS IN MACEDONIAN CHILDREN - Zafirova, Biljana; Papazova, Marija; Zivadinovik, Julija; Matveeva, Niki; Chadikovska, Elizabeta; Bitovska, Iskra (Journal of Morphological Sciences; Vol 1 No 1 (2018): JMS, 2018)
Aim . Evaluation of sex-specific differences of anthropometric varibales that were used as indicators of  nutritional status in Macedonian children aged 5. Materials and Methods . The study included 226.(113 boys and 113 girls) Macedonian children aged 5. We selected 5 anthropometrical parameters to measure (body weight, height, mid upper arm circumferences-MUAC, skinfolds thickness tricepsâ€“SFTr and subscapular-SFSc) and in addition according to the standard formulas we calculated: weight-for-age (BW), height-for-age (BH), body mass index-for-age (BMI) mid-upper-arm circumference-for-age (MUAC) and skifolds thikness (SFTr-for-age, SFSc-for-age). Results . In general results  have shown sex-specific differences in the examined parameters (BH, BW, BMI) in favour of the boys, with exception of skin-folds thickness that were higher in girls. Values of the 50th percentile in boys were as follows: 21 kg for BW, 115cm for BH, 15.48 kg/m2 for BMI, 15.5 cm for MUAC, 7mm for SFTr and 4.1mm for SFSc. The values of these parameters in girls were: 20kg for BW, 113.5 cm for BH, 15.01 kg/m2 for BMI, 7.8mm for  SFTr and 4.7 for SFSc respectively. Conclusion . These results can be used as criteria for assessment and detection of deviations in the nutritional status in Macedonian children aged 5